Death and the labyrinth - Foucault, Michel 1926-1984; Ashbery, John (London Continuum, 2007)
Death and the Labyrinth is unique, being Foucault's only work on literature. For Foucault this was "by far the book I wrote most easily and with the greatest pleasure". Here, Foucault explores theory, criticism and psychology through the texts of Raymond Roussel, one of the fathers of experimental writing, whose work has been celebrated by the likes of Cocteau, Duchamp, Breton, Robbe Grillet, Gide and Giacometti.This revised edition includes an introduction, chronology and bibliography to Foucault's work by James Faubion, an interview with Foucault, conducted only nine months before his death, and concludes with an essay on Roussel by the poet John Ashbery.